The Role of TRAIL, IP-10 and MxA in Distinguishing Acute Community-acquired Viral and Bacterial Pneumonia in Children - Gundogmus, Firat; Gayretli Aydın, Zeynep Gökçe; Karahan, Suleyman Caner; Yaman, Serap Ozer (Klinische Pädiatrie, 2025)
Acute paediatric community-acquired pneumonia (pedCAP) represents a significant burden on child health and highlights the need for accurate diagnostic tools. This study aimed to differentiate between acute community-acquired viral and bacterial pedCAP using TRAIL, IP-10, and MxA markers.The study a single-center prospective study was conducted between January 2019 to January 2020. During the follow-up period, 315 patients with paediatric community-acquired pneumonia were followed up. The analysis was performed with 52 patients aged 5 years and younger in whom pathogens were detected. 24 control groups were also included to see the change of markers in intact subjects. The patients’ medical history and samples were obtained upon hospital admission or within the first day.The mean values of MxA, TRAIL, and IP-10 differed significantly among all three groups (all p values p<0.01). The ROC analysis indicated that serum MxA, TRAIL, and IP-10 parameters had diagnostic value in predicting the differentiation of viral pedCAP from bacterial pedCAP .The TRAIL, MxA, and IP-10 markers have diagnostic value in distinguishing viral pneumonia and bacterial pneumonia. Among these markers, MxA exhibits the highest sensitivity. High levels of MxA, TRAIL and IP-10 in combination with low C-reactive protein (CRP), procalcitonin (PCT) and neutrophil lymphocyte ratio (NLR) values to differentiate viral from bacterial pedCAP will significantly contribute to the accurate identification of viral LRTI.
Keywords: myxovirus resistance protein 1 (MxA); tumor necrosis factor- related; apoptosıs-inducing ligand (TRAIL); interferon-γ-induced protein (IP-10).; Acute paediatric community-acquired pneumonia (pedCAP)